An Equivalent Fir Filter for an IIR Filter with Double Frequency Initialisation - J., Jeedella; H., Al-Ahmad; M., Al-Mualla; Noras, J.M. (INTI International University, 2009)
IIR filters designed for steady state operation suffer from the transient effect caused by processing a finite number of samples. Their performance can be improved by using initialization techniques. This letter presents an equivalent FIR filter for an IIR filter operating in the transient and using double frequency initialization. This equivalent filter simplifies the transient analysis of IIR filters and provides a direct formula for calculating the transient frequency response and usable bandwith.